Guia de depósito da biblioteca digital do TJDFT : o passo a passo para o gerenciamento de objetos digitais no software DSpace - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2021)
This guide demonstrates aspects of BDTJDFT management, in view of the use of the DSpace free software in version 6.3. Therefore, is mainly dedicated to the process of feeding the BD, whose collection has variety in its typology, including articles from subscribed magazines, court publications and intellectual production of magistrates and civil servants. In this regard, it is worth remembering that, due to the Copyright Law, access the part of the collection, concerning the subscribed magazines, is restricted. The court's publications, however, are freely accessible.
Design Gráfico, Diagramação e Ilustrações : Rafael Fernandez Gomes e Nuielle Medeiros / Normalização : Ingrid Torres Schiessl / Revisor : Flavia Karla Ribeiro Santos e Rafael Teixeira de Souza
Esta produção é um produto do Projeto de pesquisa Estudos para atualização tecnológica de ecossistema de informação do Tribunal de Justiça do Distrito Federal e Territórios.
As opiniões emitidas nesta publicação são de exclusiva e inteira responsabilidade dos autores, não exprimindo, necessariamente, o ponto de vista do Instituto Brasileiro de Informação em Ciência e Tecnologia ou do Ministério da Ciência, Tecnologia e Inovações.
Keywords: Acervo digital; Guia de usuário (manual); Sistema de informação; Processos de disseminação da informação